Enhancing Intercultural Skills Through a COIL Experience - Mickey Marsee; Jorge Eduardo Pineda Hoyos (Profile Issues in Teachers' Professional Development)
This paper describes a case study of instructional strategies employed in a collaborative online international learning experience between students from Colombia and the US to increase their understanding of cultural tolerance. The study aimed to examine student perception of their intercultural skills development, particularly in recognizing both cultural similarities and differences, as previous research suggests that students struggle with identifying differences, focusing only on similarities in exchanges. Data were collected from transcriptions of student reflection recordings and their final presentations and were analyzed using the intercultural competence dimensions and subdimensions framework. The findings suggest that participants developed cultural awareness of differences, openness, and tolerance of their own and their partners’ cultures and increased their teamwork skills.